Pivotal Phase 3 Randomized Clinical Trial of the Safety, Tolerability, and Immunogenicity of 20-Valent Pneumococcal Conjugate Vaccine in Adults Aged ≥18 Years. (23rd December 2021) - Essink, Brandon; Sabharwal, Charu; Cannon, Kevin; Frenck, Robert; Lal, Himal; Xu, Xia; Sundaraiyer, Vani; Peng, Yahong; Moyer, Lisa; Pride, Michael W; Scully, Ingrid L; Jansen, Kathrin U; et al.
Abstract: Background: Pneumococcal conjugate vaccines (PCVs) have significantly reduced pneumococcal disease, but disease from non-PCV serotypes remains. The safety, tolerability, and immunogenicity of a 20-valent PCV (PCV20) were evaluated. Methods: This pivotal phase 3, randomized, double-blind study enrolled adults into 3 age groups (≥60, 50–59, and 18–49 years) at US and Swedish sites. Participants were randomized to receive 1 PCV20 or 13-valent PCV (PCV13) dose. After 1 month, participants aged ≥60 years also received 1 dose of saline or 23-valent polysaccharide vaccine (PPSV23). Safety assessments included local reactions, systemic events, adverse events, serious adverse events, and newly diagnosed chronic medical conditions. Opsonophagocytic activity geometric mean titers 1 month after PCV20 were compared with 13 matched serotypes after PCV13 and 7 additional serotypes after PPSV23 in participants aged ≥60 years; noninferiority was declared if the lower bound of the 2-sided 95% confidence interval for the opsonophagocytic activity geometric mean titer ratio (ratio of PCV20/saline to PCV13/PPSV23 group) was >0.5. PCV20-elicited immune responses in younger participants were also bridged to those in 60–64-year-olds. Results: The severity and frequency of prompted local reactions and systemic events were similar after PCV20 or PCV13; no safety concerns were identified. Primary immunogenicity objectives were met, with immune responses after PCV20 noninferior to 13 matched serotypes after PCV13 and to 6 additional PPSV23 serotypes in participants aged ≥60 years; serotype 8 missed the statistical noninferiority criterion. PCV20 induced robust responses to all 20 vaccine serotypes across age groups. Conclusions: PCV20 was safe and well tolerated, with immunogenicity comparable to that of PCV13 or PPSV23. PCV20 is anticipated to expand protection against pneumococcal disease in adults. Clinical Trials Registration: NCT03760146. Abstract : The 20-valent pneumococcal conjugate vaccine (PCV20) was safe and well tolerated, with immunogenicity comparable to that of the 13-valent pneumococcal conjugate vaccine or 23-valent polysaccharide vaccine. PCV20 is anticipated to expand protection against pneumococcal disease in adults.